Pemikiran Fatchur Rahman Mengenai Skema Sanad Hadis Dalam Buku Ikhtisar Mushthalahul Hadits - Faisal, Ahmad; Hazaa, Zuhair Mubarrak (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
This research aims to explore more deeply the thought of Fatchur Rahman's hadith. This research is qualitative research, library research in nature, so the primary source is Fatchur Rahman's written work entitled Ikhtishar Mushthalahul Hadith. Fatchur Rahman explains the limited definition of Hadith and the definition of Hadith from a more general perspective. Fatchur Rahman doesn't seem interested in discussing more broadly the differences between Hadith and Sunna, but Fatchur Rahman is more inclined to equate Sunna and Hadith. The definition of Hadith with a limited meaning according to Fatchur Rahman is: "Something attributed to the Prophet Muhammad saw. whether in the form of words, actions, statements (taqr?r) and so on (such as the characteristics, conditions and himmah or desires of the Prophet Muhammad.)." Meanwhile, the definition of Hadith contains a broad meaning, according to Fatchur Rahman's definition, which includes all news that is marfuk (relied on the Prophet saw), mauq?f (relied on ?a??bah) and maq??? (relied on tabiin). Fatchur Rahman developed a research study on hadith sanads using the hadith sanad scheme methodology. If Muhammad Hasbi Ash-Shiddieqy had not had time to write about this, then Fatchur Rahman could be considered a pioneering example who explained how to carefully examine the framework of hadith sanad diagrams in full along with examples of hadith sanad schemes in his book entitled Ikhtishar Mushthalahul Hadith.